Understanding old herbal secrets: The renaissance of traditional medicinal plants beyond the twenty classic species? - Scherrer, Marisa Milena; Zerbe, Stefan; Petelka, Joshua; Säumel, Ina (Frontiers in Pharmacology, 2023)
The use of traditional medicinal plants plays an important role especially in remote rural and marginalized landscapes at different latitudes. In the development of nature conservation strategies based on local knowledge and sustainable resource management, medicinal herbs have been hypothesized to be cultural key stone species. Environmental education is a crucial driver for fostering environmental literacy and preserving local knowledge across generations. We conducted semi-structured interviews with stakeholders in the Autonomous Province of Bozen-South Tyrol (N Italy) to gain insights into, and reflections on, the cultural value of traditional medicinal plants and their interplay within the local landscape, nature conservation and their role in environmental education and knowledge transfer across generations. We also used a combination of purposive and snowball sampling to identify relevant actors. The different voices collected in the study clearly highlight the role of medicinal herbs in health care, for cultural identity of local communities and demonstrate a growing commercial market niche that maintains the local economy and services, including widespread offers related to environmental education, that have mot, unfortunately, been used yet in the formal curricula of local schools. The latter is crucial for a holistic approach taking medicinal plants as an ideal vehicle to connect especially children with nature and history of South Tyrol, strengthening health education and overall environmental literacy, including species knowledge. However, the revival of herbal medicine and related knowledge do not prevent the continuous loss of local traditional knowledge regarding medicinal plants, recipes and use. More species and their uses are being forgotten due to superficialisation of knowledge and of mainstreaming and homogenization of the global market of herbal medicine. Safeguarding the natural and cultural treasures of South Tyrol for future generations is in the hands of the local communities.